2013
DOI: 10.3389/fpsyg.2013.00404
|View full text |Cite
|
Sign up to set email alerts
|

Foresight beyond the very next event: four-year-olds can link past and deferred future episodes

Abstract: Previous experiments have demonstrated that by 4 years of age children can use information from a past episode to solve a problem for the very next future episode. However, it remained unclear whether 4-year-olds can similarly use such information to solve a problem for a more removed future episode that is not of immediate concern. In the current study we introduced 4-year-olds to problems in one room before taking them to another room and distracting them for 15 min. The children were then offered a choice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 54 publications
4
43
1
Order By: Relevance
“…The future children prepare for in this paradigm is the very next event, albeit one in another room. In a recent follow‐up study, we found that 4‐year‐olds similarly perform above chance even when informed that they will not be returning to the first room until a 5‐minute sand‐timer had completed its cycle . By 48 months, children can act prudently to bring about an anticipated future scenario, consistent with the developments of the episodic foresight components reviewed earlier.…”
Section: The Development Of Foresightful Behaviorsupporting
confidence: 74%
“…The future children prepare for in this paradigm is the very next event, albeit one in another room. In a recent follow‐up study, we found that 4‐year‐olds similarly perform above chance even when informed that they will not be returning to the first room until a 5‐minute sand‐timer had completed its cycle . By 48 months, children can act prudently to bring about an anticipated future scenario, consistent with the developments of the episodic foresight components reviewed earlier.…”
Section: The Development Of Foresightful Behaviorsupporting
confidence: 74%
“…They used memory of a specific past episode from a spatially removed context and prepared for a return to these problems when presented with the opportunity. This finding has been replicated in studies in which selecting the object was separated by several minutes from returning to the room with the problem . By age 4, children can remember a novel problem well enough to recognize and secure its future solution when the chance presents itself.…”
Section: The Nature and Development Of Episodic Foresightmentioning
confidence: 76%
“…Redshaw and Suddendorf, 2013) 1 . Specifically, rather than insert the delay between the original episode and the selection phase, comparative studies have inserted the delay after the selection phase (cf.…”
Section: Comparative Studiesmentioning
confidence: 99%